2021
DOI: 10.1212/nxi.0000000000000963
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic Cerebellar Degeneration

Abstract: ObjectiveInvestigate the value of including cerebellar degeneration-related protein 2-like (CDR2L) as a marker in commercial diagnostic tests for anti-Yo–associated paraneoplastic cerebellar degeneration (PCD).MethodsWe included sera and CSF samples from 24 patients with suspected PCD (6 of whom had PCD with underlying gynecologic or breast cancer), who were positive for Yo antibodies using the commercially available, paraneoplastic neurologic syndromes (PNS) 14 Line Assay from Ravo Diagnostika. The samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…In our previous study, we reported that inclusion of CDR2L as an additional Yo antibody target increases test specificity and therefore serves as an important diagnostic biomarker for Yo‐PCD [8]. In this follow‐up study, we further validated our CBA in comparison to western blot and line immunoassay techniques in a larger patient cohort and additional control groups.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…In our previous study, we reported that inclusion of CDR2L as an additional Yo antibody target increases test specificity and therefore serves as an important diagnostic biomarker for Yo‐PCD [8]. In this follow‐up study, we further validated our CBA in comparison to western blot and line immunoassay techniques in a larger patient cohort and additional control groups.…”
Section: Introductionmentioning
confidence: 84%
“…We found that the CDR2L CBA identified all 48 patients with Yo‐PCD, and was negative for the 15 non‐PCD patients, 22 patients with ovarian cancer without neurological syndromes and 50 healthy blood donors. In our previous study, 24 patient sera that tested positive for anti‐Yo by line immunoassay were evaluated by CDR2L CBA and western blot analysis with recombinant CDR2 and CDR2L proteins [8]. Only the six true‐positive anti‐Yo PCD sera tested positive in the CDR2L CBA, rendering the 18 remaining sera false positive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most laboratories use commercial line assays and /or immunohistochemistry to detect CRMP5 antibodies. While line assays are easy to perform, they can give false positive results ( 9 , 10 , 16 ). Therefore, another confirmatory test is needed for the line assays.…”
Section: Discussionmentioning
confidence: 99%